Observed heterospecific clutch size can affect offspring investment decisions - Forsman, Jukka T. (The Royal Society, 2012)
Optimal investment in offspring is important in maximizing lifetime reproductive success. Yet, very little is known how animals gather and integrate information about environmental factors to fine tune investment. Observing the decisions and success of other individuals, particularly when those individuals initiate breeding earlier, may provide a way for animals to quickly arrive at better breeding investment decisions. Here we show, with a field experiment using artificial nests appearing similar to resident tit nests with completed clutches, that a migratory bird can use the observed high and low clutch size of a resident competing bird species to increase and decrease clutch size and egg mass, accordingly. Our results demonstrate that songbirds can discriminate between high and low quantity of heterospecific eggs, and that social information can have long-term physiological consequences affecting reproductive strategies. Such behaviour may help animals to better adapt to changing environments and lead to convergent traits with competitors.